Diseminasi Olah Latih Vinegar Alami dari Ballo - Nining Wahyuni; Andi Muhammad Irfan Taufan Asfar; Andi Muhamad Iqbal Akbar Asfar; Asrina Asrina; Isdar Isdar (Unri Conference Series: Community Engagement, 2021)
Bulu Ulaweng Village is a mountain village that is overgrown with palm trees. There are 20 household heads who work as sugar palm farmers. Where the average community processes 4-5 palm trees for production, so that in a day they will produce as much as 560 L of palm juice. Until now, the remaining sap for making shell sugar and ballo drinks has not been solved. Utilization of the remaining juice into vinegar is a form of counseling by the community service team at the University of Muhammadiyah Bone. The existence of this innovation can be a solution for partners' problems regarding the utilization of the remaining palm sap and has a high selling value. This counseling was attended by 7 people consisting of Women community of PKK Bulu Ulaweng Village. The activities carried out were in the form of an introduction to the purpose of holding training dissemination through community service activities, exposure to tools and materials and the stages of making natural vinegar from ballo. So that the community will be able to implement it independently as the end result of this counseling.